Opportunity 08 : independent ideas for America's next president (Brookings Institution Press, 2008)
"Answers the call for nonpartisan discussion on challenges that matter most to the future of our society, our prosperity, and our world, including Iran and Iraq, China's rise, poverty and equality, health care reform, and retirement security. New topics added include homeland security, foreign aid, and relations with Pakistan"--Provided by publisher